Management of Customary Forests as Community-Based Ecotourism Areas in Tenganan Pegringsingan Village Karangasem Bali - Putu Sri Murtini; Syamsul Alam Paturusi; Ida Bagus Gde Pujaastawa (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
Tenganan Pegringsingan Village's customary forest is well preserved because it is regulated by customary regulations called Awig-awig. This research on customary forest management as a community-based ecotourism area in Tenganan Pegringsingan Village aims to identify the potential of customary forests that can be managed as an ecotourism attraction, analyze the management system and the implications that occur and analyze the driving factors and inhibitors of customary forest management. The method used in this research is the qualitative description and Force Field Analysis. The results showed that the existing potential is in the form of natural potential, socio-cultural, and artificial potential. The customary forest management system is based on awig-awig applied by Tenganan Pegringsingan village and sustainable development supported by local community organizations. The key success factor obtained is that the development of customary forest ecotourism in Tenganan Pegringsingan Village is carried out optimally to become promising ecotourism while maintaining existing sustainability.